Class Inequality in the Global City Migrants, Workers and Cosmopolitanism in Singapore - Ye, Junjia; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
In striving to become cosmopolitan, global cities aim to attract highly-skilled workers while relying on a vast underbelly of low-waged, low status migrants. This book tells the story of one such city, revealing how national development produces both aspirations to be cosmopolitan and to improve one's class standing, along with limitations in achieving such aims. Through the analysis of three different groups of workers in Singapore, Ye shows that cosmopolitanism is an exclusive and aspirational construct created through global and national development strategies, transnational migration and individual senses of identity. This dialectic relationship between class and cosmopolitanism is never free from power and is constituted through material and symbolic conditions, struggles and violence. Class is also constituted through 'the self' and lies at the very heart of different constructions of personhood as they intersect with gender, race, sexuality, ethnicity and nationality.
Keywords: Economic development; Migration; Sociology of Work; Social Structure, Social Inequality